Bridging the Divide: Exploring Why Nigerian Men Struggle with Prostate Cancer Awareness and Screening Uptake (IPS Journal of Public Health, 2025)
Background: Fruits and vegetables are crucial sources of vitamins and minerals, promoting good health. However, when consumed unclean, they can pose risks, particularly in rural communities of developing countries where intestinal parasitic diseases are endemic, leading to significant economic and public health consequences.Methods: 500 fruit and vegetable samples were collected and washed separately in 10% formal-saline water. The sedimentation method concentrated parasites, which were then examined using a light microscope. Data entry and analysis were performed using SPSS version 21.0. Pearson chi-square was employed to compare the rate of parasitic contamination among different types of fruits and vegetables and assess the association between parasite species and vegetable type.Results: Of the 500 samples, 105 (21.0%) were contaminated with at least one type of parasite. Strongyloides (5.2%) and Ascaris lumbricoides (3.8%) were the most frequently detected parasites, while Hymenolepis diminuta and Trichostrongylus (1.4%) were the least detected. African cherry (80.0%) was the most infested fruit, and Jute mallow (100.0%) was the most infested vegetable. Itoku market had the highest infestation rate (25.0%) of intestinal parasites on fruits and vegetables, while Adatan market had the lowest (17.0%). Parasitic contamination was significantly different among samples (p
Keywords: Prostate cancer; Nigerian men; screening; awareness; barriers; facilitators